2015
DOI: 10.1097/mlr.0000000000000390
|View full text |Cite
|
Sign up to set email alerts
|

Does Mandating Nursing Home Participation in Quality Reporting Make a Difference? Evidence From Massachusetts

Abstract: Background Quality report cards have been shown to be effective in influencing patients' referrals and promoting quality improvement in some instances and not others. In this study we investigate one of the mechanisms that may detract from their effectiveness: voluntary versus mandatory participation of nursing homes in public quality reporting. Objectives To answer two questions: 1) Were the nursing homes choosing not to participate low quality performers relative to those who chose to participate? 2) Once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Competing HHAs are expected to compete on quality, especially on publicly reported, and hence observed, SQMs, because price competition is limited when most patients are insured. A similar phenomenon has been observed for nursing homes where publication of QMs in Nursing Home Compare influenced referrals, and led nursing homes to bring their QMs in line with those of their competitors (Kim, 2016;Mukamel et al, 2015). Table 3 shows that all incremental F statistics in the first stage models (included in the appendix, available in the online Supplemental Material) range from 18.3 to 441.1, exceeding the critical value of F >10 required for rejection of the weak IV hypothesis (Staiger & Stock, 1997).…”
Section: Variablessupporting
confidence: 58%
“…Competing HHAs are expected to compete on quality, especially on publicly reported, and hence observed, SQMs, because price competition is limited when most patients are insured. A similar phenomenon has been observed for nursing homes where publication of QMs in Nursing Home Compare influenced referrals, and led nursing homes to bring their QMs in line with those of their competitors (Kim, 2016;Mukamel et al, 2015). Table 3 shows that all incremental F statistics in the first stage models (included in the appendix, available in the online Supplemental Material) range from 18.3 to 441.1, exceeding the critical value of F >10 required for rejection of the weak IV hypothesis (Staiger & Stock, 1997).…”
Section: Variablessupporting
confidence: 58%
“…23 Other researchers have found that mandating NH participation in quality improvement initiatives is more effective than voluntary efforts alone. 24 As described by Rogers, innovation decisions made by an authority (in this case, CMS) are responsible for the fastest rate of adoption, as opposed to collective or optional decisions to adopt. 12 Given that, along with recent findings and past research, requiring NHSN reporting could increase staffing and resources to prevent infections in NHs and increase capacity to improve resident quality of life and health care outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, it was found that the benefits were perceived in centers that participated on a voluntary basis but also in centers that participated on a mandatory basis. The main reason for not wanting to participate was the workload involved or the absence of a professional to take responsibility for this task [ 233 ].…”
Section: Should the Health Authority Require A Set Of Data Like The O...mentioning
confidence: 99%